This preview shows page 1. Sign up to view the full content.
Unformatted text preview: I = ˙ K + δ K S = sY ˙ K + δ K = sY K (0) = K Now differentiate the variable k with respect to time, i.e., derive dk / dt , dk dt = ˙ k = L dK dt − K dL dt L 2 ˙ k = ± 1 L ² dK dt − ± K L ²± 1 L ² dL dt = ± K L ²± 1 K ² dK dt − ± K L ²± 1 L ² dL dt = k ± ˙ K K − ˙ L L ² But ˙ K K = sY − δ K K = sY L ± L K ² − δ = sf ( k ) k − δ and ˙ L L = nL L = n Hence ˙ k = sf ( k ) − δ k − nk = sf ( k ) − ( n + δ ) k (2.11)...
View
Full
Document
This note was uploaded on 12/14/2011 for the course ECO 3023 taught by Professor Dr.gwartney during the Fall '11 term at FSU.
 Fall '11
 Dr.Gwartney
 Economics

Click to edit the document details